Labor Market Reforms and Earnings Dynamics : the Italian Case. (IMF Working Papers; Working Paper ;, 2021)
This paper summarizes statistics on the key aspects of the distribution of earnings levels and earnings changes using administrative (social security) data from Italy between 1985 and 2016. During the time covered by our data, earnings inequality and earnings volatility increased, while earnings mobility did not change significantly. We connect these trends with some salient facts about the Italian labor market, in particular the labor market reforms of the 1990s and 2000s which induced a substantial rise in fixedterm and part-time employment. The rise in parttime work explains much of the rise in earnings inequality, while the rise in fixed-term contracts explains much of the rise in volatility. Both these trends affect the earnings distribution through hours worked: part-time jobs reduce hours worked within a week, while fixed-term contracts reduce the number of weeks worked during the year as well as increase their volatility. We find weak evidence that fixed-term contracts represent a "stepping-stone" to permanent employment. Finally, we offer suggestive evidence that the labor market reforms contributed to the slowdown in labor productivity in Italy by delaying human capital accumulation (in the form of general and firm-specific experience) of recent cohorts.